Farewells and language usage: Multilingual practices in Bolzano merchants’ documents - Meluzzi, Chiara (Cuadernos de Filología Italiana, 2022)
Research on historical sociolinguistics has seen letter writing as a social practice which could present many instances of multilingualism. Merchants’ language management is also of particular importance for the role of traders in language contact and change. In this work, merchants’ correspondence from the town of Bolzano will be considered across the 18th and 19th century, by considering letters written by the Georg Anton Menz textile company to its correspondents. These letters have been preserved (and partly digitalized) in the archive of the Chamber of Commerce in Bolzano. The analysis will focus on language distribution, as well as on multilingual practices in closing formulas. It will be shown how the relative status of the languages involved changed over time, and how an Italian closing formula (addio, farewell) was used also to close German letters. This probably correlates on a specific writing style in use in the Habsburg Empire but uncommon for Italian commercial letters.